2014
DOI: 10.1097/cad.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

MiR-489 modulates cisplatin resistance in human ovarian cancer cells by targeting Akt3

Abstract: MicroRNAs are a conserved class of small noncoding RNA molecules that harbour the capacity to regulate protein-coding gene expression at the post-transcriptional level. In the current study, we show that miR-489 is downregulated in cisplatin (CDDP)-resistant ovarian cancer cells, SKOV3/CDDP and OVCAR3/CDDP cells. MiR-489 overexpression results in an inhibition of SKOV3 and OVCAR3 cell survival and cell growth after CDDP treatment and an induction of cell apoptosis. Inhibition of miR-489 yields the opposite res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…These 3′-UTR motifs are recognized by the following microRNAs: miR-527, miR-374, miR-520F, miR-513, miR-142-5p, miR-507, miR-369-3p, miR-491, miR-511, miR-489, miR-432, miR-28, miR-520G and miR-520H. It is worth noting that every microRNA from this set had been associated with other oncological diseases including breast [3336], ovarian [37, 38], colorectal cancers [3941], glioblastoma [42, 43], non-small cell lung cancer [44, 45] and others.…”
Section: Resultsmentioning
confidence: 99%
“…These 3′-UTR motifs are recognized by the following microRNAs: miR-527, miR-374, miR-520F, miR-513, miR-142-5p, miR-507, miR-369-3p, miR-491, miR-511, miR-489, miR-432, miR-28, miR-520G and miR-520H. It is worth noting that every microRNA from this set had been associated with other oncological diseases including breast [3336], ovarian [37, 38], colorectal cancers [3941], glioblastoma [42, 43], non-small cell lung cancer [44, 45] and others.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, miR-489 functions as a tumor suppressor in hypopharyngeal squamous cell carcinoma and suppresses growth of cancer cells by targeting protein tyrosine phosphatase, non-receptor type 11 (PTPN11) [17]. Moreover, miR-489 regulates ovarian cancer cell survival, growth and apoptosis via suppression of Akt3 [18]. miR-489 loss promotes invasion and epithelial-mesenchymal transition (EMT) events of lung cancer cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that miRNAs play pivotal roles in various cellular processes including apoptosis, proliferation, motility and differentiation [11–15]. miR-489 has been found to be underexpressed in breast cancer [16], hypopharyngeal squamous cell carcinoma [17], ovarian cancer [18], lung cancer [19] and hepatocellular carcinoma (HCC) [20]. However, miR-489 is prominently upregulated in oral squamous cell carcinoma [21], clear cell renal cell carcinoma [22, 23], suggesting that the expression and role of miR-489 are variability in different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…let-7e [258], miR-29 [259], miR-128 [260], miR-136 [261], miR-155 [262], miR-199a [263], miR-216b [264], miR-449a [265], miR-489 [266], miR-595 [267], miR-634 [268] and miR-770 [269] inversely correlate with cisplatin resistance in OC while miR-218 [270, 271] increases sensitivity to cisplatin in CC cells. miR-21 [272, 273], miR-125b [274], miR-214 [160], miR-224 [275], miR-376c [276] and miR-509 [277] induce cisplatin resistance in OC.…”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%